Behind the Gates: Life, Security, and the Pursuit of Happiness in Fortress America - Low, Setha (Routledge, 2003)
First Published in 2003. Routledge is an imprint of Taylor & Francis, an informa company. Setha Low is Professor of Anthropology and Environmental Psychology at the CUNY Graduate Center. She is the author or editor of numerous books, including Theorizing the City: The New Urban Anthropology Reader ; Housing, Culture, and Design ; Cultural Spaces ; and Place Attachment. "Provocative and disturbing, this much-needed book holds up an unsparing mirror to an unsettling sign of our times." - The New York Times